Degradation of Polyester Composite Reinforced E-Glass Fiber with Calcium Carbonate Filler in Seawater - Nasir, Mohamad; Fajrin, Jauhar (International Journal of Membrane Science and Technology, 2023)
This research is concerned with composite materials that use CaCO3 as a reinforcing material in construction, especially subsea panels and buildings. Composite materials are solids composed of two or more materials that have their own properties and improve their properties when combined. In this experiment, glass fiber and CaCO3 were mixed in a certain composition and tested to evaluate the water absorption and mechanical strength of the composite. The results show that increasing temperature can increase water absorption, while the addition of CaCO3 has a significant effect on water absorption due to its hydrophilic properties. Water absorption in polyester composites is influenced by aging temperature and Calcium Carbonate powder filler, affecting tensile and bending strength. As aging temperature increases, mechanical strength decreases, composite having the highest tensile strength. Bending tests show debonding and splitting fault patterns due to glass fiber arrangement. With a deeper understanding of how CaCO3 affects composite materials under various conditions, this research can provide valuable insights for developing more durable composite materials suitable for construction applications, especially in corrosive environments such as subsea buildings.In this research, it proposes theoretically model to controlling on half-wave voltage of modulator, in which it uses studying the factor of effective of refractive index difference, this using analysis distribution of refractive index for LN material before and after voltage is applied (i.e., with and without applied voltage), and uses analysis a factor of propagation constant difference ??, before and after voltage is applied where it depends on the wavelength, these leads to it controls on the half-wave voltage V? using a reduction half-wave voltage up to 1V. Also, it achieves an excellent solution for solve the fundamental optical mode with effective factor is neff. Finally, the modulator with an effect effective refractive index difference have lower applied voltage up to 10V, and with an effective propagation constant difference the operating voltage is from value of 20V.